1985
DOI: 10.1152/ajpcell.1985.249.3.c256
|View full text |Cite
|
Sign up to set email alerts
|

ATP depletion and loss of cell integrity in anoxic hepatocytes and silica-treated P388D1 macrophages

Abstract: The relationship between ATP depletion and the loss of cell integrity was examined in the killing of hepatocytes by anoxia and P388D1 macrophages by silica. ATP depletion is a feature of the reaction to either hazard. Treatment of hepatocytes, however, with antimycin, oligomycin, sodium azide, or N,N'-dicyclohexylcarbodiimide produced a rate and extent of ATP depletion comparable with anoxia without significant loss of viability. Treatment of P388D1 cells with 2-deoxyglucose plus antimycin, oligomycin, or sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Miti gating this, however, is the fact that oxidantstressed cells are not 'resting'. Past studies have shown that an early response of cells to a number of injurious agents including H2O2 is a rapid depletion of intracellular ATP stores [13,14], Studies in our laboratory confirmed this in H202-treated RPAEC [15]. Within 10 min of exposure to H2O2, greater than 75% of the cellular ATP was lost.…”
Section: Effects Of Xo Inhibitors On Neutrophil-mediated Killing Ofsupporting
confidence: 62%
“…Miti gating this, however, is the fact that oxidantstressed cells are not 'resting'. Past studies have shown that an early response of cells to a number of injurious agents including H2O2 is a rapid depletion of intracellular ATP stores [13,14], Studies in our laboratory confirmed this in H202-treated RPAEC [15]. Within 10 min of exposure to H2O2, greater than 75% of the cellular ATP was lost.…”
Section: Effects Of Xo Inhibitors On Neutrophil-mediated Killing Ofsupporting
confidence: 62%
“…Measurement of ATP Content-The cellular ATP content was determined by modification of the firefly luciferin-luciferase method as described previously (16). Briefly, cells in RPMI medium from 24-well plates were transferred into 1.5-ml microcentrifuge tubes, and 20 l of trichloroacetic acid was added to give a final concentration of 3%.…”
Section: Figmentioning
confidence: 99%
“…ATP was quantitated using the luciferin/luciferase assay (Kane et al, 1985). Bioluminescence was quantitated in a luminescence spectrometer (model LS-50; Perkin-Elmer Corp., Norwalk, CT).…”
Section: Solutionsmentioning
confidence: 99%